Correlation between Lifestyle Factors, Body Fat Composition and Biological Age - Muti Indah Asmira; Yunus Elon (GLOBAL HEALTH SCIENCE GROUP, 2024)
Living a healthy lifestyle considers various components that influence daily life. In contrast, an unhealthy lifestyle may lead to changes in body fat composition and biological age. This study aims to analyze the relationship between lifestyle with the distribution of body fat components and biological age. This cross-sectional quantitative was carried out in Cihanjuang Rahayu Village on men and women aged 30-60 years. Using the purposive sampling technique, 157 respondents was selected based on the predetermined age criteria. Data collection involved a questionnaire to assess lifestyle data, while an Omron device measured body fat composition. The data were analyzed using the Spearman correlation test with a significance level of 0,05. This study found no significant relationship between lifestyle and body fat composition in the subcutaneous tissue and legs (P-value > 0,05). However, a significant relationship was observed between a healthy lifestyle and body fat composition in trunk, arms, and biological age (P-value < 0,05). The findings of this study demonstrate a significant association between a healthy lifestyle and body fat distribution, especially in the trunk, arms, and biological age. Conversely, no significant relationship was found between lifestyle and body fat composition in the subcutaneous area or legs. These findings suggest that a healthy lifestyle can influence specific aspects of body composition, particularly in certain body regions.